BenchPress: Dynamic Workload Control in the OLTP-Bench Testbed - Aken, Dana Van; Difallah, Djellel E.; Pavlo, Andrew; Cudré-Mauroux, Philippe; Curino, Carlo (International Conference on Management of Data, 2015)
Benchmarking is an essential activity when choosing database products, tuning systems, and understanding the trade-offs of the underlying engines. But the workloads available for this effort are often restrictive and non-representative of the ever changing requirements of the modern database applications. We recently introduced OLTP-Bench, an extensible testbed for benchmarking relational databases that is bundled with 15 workloads. The key features that set this framework apart is its ability to tightly control the request rate and dynamically change the transaction mixture. This allows an administrator to compose complex execution targets that recreate real system loads, and opens the doors to new research directions involving tuning for special execution patterns and multi-tenancy. In this demonstration, we highlight OLTP-Bench's important features through the BenchPress game. It allows users to control the benchmark behavior in real time for multiple database management systems.